2009
DOI: 10.1111/j.1469-8749.2009.03271.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional performance of children with developmental coordination disorder at home and at school

Abstract: This study investigated the functional performance of daily activities at home and at school in a population-based sample of children with different degrees of motor coordination impairment and competence. Sixteen children (seven males, nine females; mean age 8 y, SD 9 mo) with developmental coordination disorder (DCD), 25 with suspected DCD ([sDCD] 17 males, eight females; mean age 7 y 6 mo, SD 8 mo), and 63 children without motor problems (39 males, 24 females; mean age 7 y 9 mo, SD 7 mo) were recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 28 publications
1
65
0
5
Order By: Relevance
“…Alternatively, depending on the support and attitudes of parents and immediate family members, the manifestation of functional problems may not be evident in the home situation if children are not challenged enough to do things for themselves. In a study by Wang (2009) no significant correlation was found between functional performance at home and at school in children with motor coordination problems [104].…”
Section: Support and Relationshipsmentioning
confidence: 91%
“…Alternatively, depending on the support and attitudes of parents and immediate family members, the manifestation of functional problems may not be evident in the home situation if children are not challenged enough to do things for themselves. In a study by Wang (2009) no significant correlation was found between functional performance at home and at school in children with motor coordination problems [104].…”
Section: Support and Relationshipsmentioning
confidence: 91%
“…such as handwriting, dressing, tying shoelaces, using utensils, throwing and/or catching a ball, and participating in sports or other physical activities (American Psychiatric Association, 2000;Magalhães et al, 2011;Wang et al, 2009;Zwicker et al, 2012). Evidence has shown that compared to typically developing children, children with DCD have lower participation in moderate to vigorous physical activity and instead prefer to spend their energy on low intensity physical activity Jarus et al, 2011;Poulsen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…At home, difficulties with dressing can manifest in tasks such as manipulating buttons and zips, where fine motor manipulation and organisational skills are required (Roger et al, 2003). Within the school environment, these difficulties transfer into a range of school activities (Wang et al, 2009), in particular, handwriting, which is significantly impacted (Miller et al, 2001). Handwriting difficulties are mentioned in the formal diagnostic criteria for DCD (APA, 2000), are frequently mentioned in parent and teacher reports and are the most common reason for referral to occupational therapy for this population (Asher, 2006).…”
Section: Introductionmentioning
confidence: 99%